PHARMACOGNOSTIC AND TOXICITY STUDY OF LEPTADENIA HASTATA (Pers.) Decne (Asclepiadaceae) ROOT - Namadina, Murtala M.; Nuhu, A. A.; Yunusa, A. Y.; Okrikata, E.; Ekong, N. J.; Abdulsalami, H. (FUDMA JOURNAL OF SCIENCES, 2023)
Leptadenia hastata an African plant species used in traditional medicine as an anti-venom, antihypertensive, anti-diabetic, analgesic and also used for catarrh and skin disease. Despite the fact that the root of Leptadenia hastata have several medicinal properties, no standardization parameter has been assessed. The study was aimed at establishing a safety profile, evaluating phytochemical constituents and some Pharmacological properties of root extract of L. hastata. Evaluation of the powdered sample (chemomicroscopic, physicochemical parameters), qualitative and quantitative phytochemical analysis and acute toxicity study was carried out using standard methods. Chemomicroscopic characters present included; cellulose cell wall, lignified cell wall, tannins, starch, calcium oxalate and cutin. The physicochemical parameters evaluated included: moisture content (7.3%), total ash (10.33%), water soluble (7.0%), acid insoluble ash (5.37%), ethanol extractive value (13.33%) and water extractive value (10.33%).Trace metals which included Pb, Zn, Cd, Cu and Mn detected in L. hastata were below the FAO/WHO (1984) permissible limit for edible plants. Phytochemicals which include alkaloids, flavonoids, saponins, phenols, tannins, glycosides, carbohydrates and triterpenes were detected in both aqueous and methanolic extracts. Steroid was absent in both extracts. The quantitative phytochemical analysis showed that tannins (298 mg/g) was the highest phytochemical detected while the lowest was saponins (6.0 mg/g). LD50 was above 5000 mg/kg and did not cause mortality in all the tested rats. The results of this investigation may be useful for deriving doses that are safe for human consumption medicinally of L. hastata.
Keywords: Leptadenia hastata, Pharmacological, Chemomicroscopic characters, Phytochemicals